2019
DOI: 10.13168/cs.2019.0037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene and Carbon Fiber on Repairing Crack of Concrete by Electrodeposition

Abstract: For many years, researches have investigated concrete repair technologies including epoxy resin injection technology, bioremediation technology and self-healing technology. However, these repair methods have proven to be expensive and cumbersome to be carry out. A more recent technology electrochemical deposition, the focus of this paper emphases in a new way of healing concrete cracks that restores durability and mechanical strength of a concrete structure. Therefore, the emphasis of the research work reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In addition, graphene materials’ excellent electrical and thermal conductivity provides new possibilities for crack control and self-healing of concrete, as shown in Figure 6 . Yang [ 85 ] took the internal structure of the reinforced concrete in seawater as the cathode and the platinum electrode as the anode. By using hybrid graphene materials, the electrochemical deposition efficiency is enhanced.…”
Section: Durabilitymentioning
confidence: 99%
“…In addition, graphene materials’ excellent electrical and thermal conductivity provides new possibilities for crack control and self-healing of concrete, as shown in Figure 6 . Yang [ 85 ] took the internal structure of the reinforced concrete in seawater as the cathode and the platinum electrode as the anode. By using hybrid graphene materials, the electrochemical deposition efficiency is enhanced.…”
Section: Durabilitymentioning
confidence: 99%
“…It can be seen that crack closure rates calculated by the mechanical-transport-chemical model are in good agreement with experimental results. The crack closure rate is F I G U R E 8 A comparison between the closure pattern of crack with 0.5 mm width in Yang et al (2019) experimental data and numerical results over 3 weeks faster in the first 5 days and gradually becomes slower. This decreasing crack closure rate can be explained by two reasons.…”
Section: Crack Closure Rate and Patternmentioning
confidence: 99%
“…The comparison of crack closure patterns from the calculated results to the experiment by Yang et al (2019) is shown in Figure 8. In their experiment, only the cracked surface was exposed in an electrolyte, while the other five surfaces are sealed with resin.…”
Section: Crack Closure Rate and Patternmentioning
confidence: 99%
See 2 more Smart Citations